Present Status and Utilization of the Mineral Resources in Nepal - Paudel, Devi Prasad (The Third Pole: Journal of Geography Education, 2019)
This paper explores the present status and utilization trends of the mineral resources in Nepal. It is mainly due to mineral resources are playing vital role in the development of economy, industry and gross domestic products (GDP). However, the mineral resources are unevenly distributed across the geographical regions. In addition, some minerals are deposited in a particular place on a small scale. As a result, Nepal has not been able to mobilize mineral resources due to lack of detailed study. It requires rigorous study to identify the amount and quantity of mineral deposits in a particular area that can be dug out for commercial purpose. The data were mainly generated from a review of various materials and concludes that the government should give high priority to explore, excavate the mineral resources. It requires clear policy efforts and provisions regarding roles and responsibilities towards the proper mobilization of mineral resources through both private and public sectors. The commercial extraction of mineral resources helps to import substitution, industrial development, jobs creation and revenue collection.